Locked Lateral Plating Versus Retrograde Nailing for Distal Femur Fractures: A Multicenter Randomized Trial. Issue 2 (February 2023) - Dunbar, Robert P.; Egol, Kenneth A.; Jones, Clifford B.; Ertl, Jan P.; Mullis, Brian; Perez, Edward; Collinge, Cory A.; Ostrum, Robert; Humphrey, Catherine; Gardner, Michael J.; Ricci, William M.; Phieffer, Laura S.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: The 2 main forms of treatment for distal femur fractures are locked lateral plating and retrograde nailing. The goal of this trial was to determine whether there are significant differences in outcomes between these forms of treatment. Design: Multicenter randomized controlled trial. Setting: Twenty academic trauma centers. Patients/Participants: One hundred sixty patients with distal femur fractures were enrolled. One hundred twenty-six patients were followed 12 months. Patients were randomized to plating in 62 cases and intramedullary nailing in 64 cases. Intervention: Lateral locked plating or retrograde intramedullary nailing. Main Outcome Measurements: Functional scoring including Short Musculoskeletal Functional Assessment, bother index, EQ Health, and EQ Index. Secondary measures included alignment, operative time, range of motion, union rate, walking ability, ability to manage stairs, and number and type of adverse events. Results: Functional testing showed no difference between the groups. Both groups were still significantly affected by their fracture 12 months after injury. There was more coronal plane valgus in the plating group, which approached statistical significance. Range of motion, walking ability, and ability to manage stairs were similar between the groups. Rate and type of adverse events were not statistically different between the groups. Conclusions: Both lateral locked plating and retrograde intramedullary nailing are reasonable surgical options for these fractures. Patients continue to improve over the course of the year after injury but remain impaired 1 year postoperatively. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.